Keynes's Europeanism as Shown in "The Economic Consequences of the Peace" - Diana Popescu; Ileana Tache (CES Working Papers, 2012)
European integration and enlargement, in the context of decreasing support of European country nationals, needs great men and great ideas standing with. J.M.Keynes proves in his book”The Economic Consequences of the Peace” that there is no other way for Europe than acts together. His economic reasons for which European countries “throb together” are presented here and supported with data. This article, with a historical approach, brings another important and strong view on the side of Europeanism.
Keywords: B22; E32; F44; 330; Keynes; business cycle; Europeanism Romania